Análisis del riesgo de introducción de Fusarium oxysporum f.sp. cubense Raza 4 Tropical (Foc R4T) plaga cuarentenaria para el Ecuador. - Gallo Lara, Mónica Andrea (2021)
The presence of Fusarium oxyporum f.sp. cubense Raza 4 Tropical (Foc R4T) in the American continent becomes a new reality for all musaceae producers on the continent, since the story is divided in two, before the presence of the plague in Colombia and after its report official in August 2019, for this reason the immediate need to carry out this degree work is created, in order to determine the risk levels of introduction of Foc R4T, as well as the phytosanitary and mitigation measures associated with the different pathways of income adapting the methodology of the Work Guide for the preparation of Pest Risk Analysis (PRA) studies by Plague, prepared and approved by Agrocalidad under Resolution 0002 of January 2020. As results, adequate phytosanitary measures were identified that will help to prevent the entry of the pest to Ecuador according to the main routes of dispersion of the fungus identified as contaminated materials of soil, water and plant material. Among the proposed measures, the mobilization of plant propagation material, identification of the origin of the material, mobilization of passengers and means of transport, as well as additional declarations in the phytosanitary export certificates from their origin, among others, were analyzed.